The Criminal Sanctions For Terrorism Crime Based On Terrorism Eradication Law And Islamic Law - Wahyu Sriyono; Lathifah Hanim (Universitas Islam Sultan Agung, 2021)
The crime of terrorism is a crime that is very dangerous for the sovereignty of the state and causes many victims. Seeing the very dangerous impact, the perpetrators of terrorism must be given heavy criminal sanctions. This study aims to identify and examine criminal sanctions for perpetrators of criminal acts of terrorism based on Act No. 5 of 2018 and Islamic Law. This study uses a normative juridical approach, which is descriptive analysis. The data used is secondary data obtained through literature study, which is then analyzed qualitatively. The results of this study are criminal sanctions for perpetrators of criminal acts of terrorism based on Act No. 5 of 2018 are capital punishment, imprisonment, confinement, and criminal fines for corporations, while according to Islamic law perpetrators of criminal acts of terrorism are threatened with a hudud finger. This crime of terrorism is also included in the qishash finger which is sentenced to death if there is no pardon (amnesty).